A review on experimental investigations of peat stabilization - Wong, Leong Sing; Hashim, Roslan; Ali, Faisal (American-Eurasian Network for Scientific Information, Jordan, 2009)
Thorough experimental investigation of stabilized peat is of great importance in order to formulate an effective mix design that can be applied for deep peat stabilization, which forms economical deep foundation for supporting highway embankments and light structures constructed on deep peat ground. Unsuitable and inadequate binders mixed with peat was often found to be the main reason for the failure in the formation of high strength stabilized peat columns. Since the properties of peat differ from location to location, reactivity of peat to a binder to form high strength stabilized peat is very site specific and requires detail laboratory mix design investigation. Despite of that, not much research is done on stabilized peat mainly because peat is problematic due to its high organic content. Consequently, it is not easy to stabilize the soil as the soil is highly acidic and stabilization of peat with cement only is often unsucessful due to insufficient binder dosage resulting in the retardation of hydration and secondary pozzolanic reactions in the stabilized soil. In order to develop a proper understanding on the reactivity of peat with various types of binder, this paper reviews the results of experimental investigation of stabilized peats developed by some researchers. Publication.